2022
DOI: 10.1142/s021797922250237x
|View full text |Cite
|
Sign up to set email alerts
|

Second-grade nanofluid flow above a vertical slandering Riga surface with double diffusion model

Abstract: The research of non-Newtonian fluids has gained the attention of scientists because of its assorted uses in biological sciences, drug reduction, damping device production and industry. Second-grade nanofluid is one of the non-Newtonian fluids. This study includes the study of second-grade nanofluid flow passing through a stretchable vertical Riga surface of variable thickness. Thermal conductivity and viscosity are taken as variables, as the function of temperature. For heat transfer, this study includes the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…15 and 16 for C(t), and A(t), respectively. The basic flow equations of Nano liquid are [34][35][36][37][38][39]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 and 16 for C(t), and A(t), respectively. The basic flow equations of Nano liquid are [34][35][36][37][38][39]:…”
Section: Resultsmentioning
confidence: 99%
“…With bounded conditions [34,36,37,40] ũ| y=0 = u w = cx, ṽ| y=0 = −v 0 , w| y=0 = 0, T| y=0 = Tw , C| y=0 = Cw ũ| y=h = 0, ṽ| y=h = 0, w| y=h = 0, T| y=h = Tl , C| y=h = Cl .…”
Section: Resultsmentioning
confidence: 99%
“…Sultan et al 29 examined the implications of activation energy in conjunction with nanoparticles and theoretical aspects of thermophoresis and Brownian diffusion. Nadeem et al 30 have focused on convective heat transfer and mass flow rate in a second‐grade fluid model incorporating tiny metallic nanoparticles with Cattaneo–Christov theory and buoyancy forces effects. Guedri et al 31 investigated the effects of various factors which includes microrotation, mixed convection mass flux, and internal heat generation/absorption, on third‐grade fluid flow governed by an extended plat surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the energy curve declines due to the influence of the velocity slip parameter. Nadeem et al [22] deliberated the nanoliquid flow that occurs when Brownian motion and the magnetic field are present across an extensible Riga surface of variable thickness. Abbas et al [23,24] described an incompressible steady Micropolar fluid flow over an irregular, vertically extending Riga sheet.…”
Section: Introductionmentioning
confidence: 99%